Fam208a orchestrates interaction protein network essential for early embryonic development and cell division - Gresakova, Veronika; Novosadova, Vendula; Prochazkova, Michaela; Bhargava, Shohag; Jenickova, Irena; Prochazka, Jan; Sedlacek, Radislav (Experimental cell research, 2019)
Maintenance of genome stability is essential for every living cell as genetic information is repeatedly challenged during DNA replication in each cell division event. Errors, defects, delays, and mistakes that arise during mitosis or meiosis lead to an activation of DNA repair processes and in case of their failure, programmed cell death, i.e. apoptosis, could be initiated. Fam208a is a protein whose importance in heterochromatin maintenance has been described recently. In this work, we describe the crucial role of Fam208a in sustaining the genome stability during the cellular division. The targeted depletion of Fam208a in mice using CRISPR/Cas9 leads to embryonic lethality before E12.5. We also used the siRNA approach to downregulate Fam208a in zygotes to avoid the influence of maternal RNA in the early stages of development. This early downregulation increased arresting of the embryonal development at the two-cell stage and occurrence of multipolar spindles formation. To investigate this further, we used the yeast two-hybrid (Y2H) system and identified new putative interaction partners Gpsm2, Amn1, Eml1, Svil, and Itgb3bp. Their co-expression with Fam208a was assessed by qRT-PCR profiling and in situ hybridisation [1] in multiple murine tissues. Based on these results we proposed that Fam208a functions within the HUSH complex by interaction with Mphosph8 as these proteins are not only able to physically interact but also co-localise. We are bringing new evidence that Fam208a is multi-interacting protein affecting genome stability on the level of cell division at the earliest stages of development and also by interaction with methylation complex in adult tissues. In addition to its epigenetic functions, Fam208a appears to have an additional role in zygotic division, possibly via interaction with newly identified putative partners Gpsm2, Amn1, Eml1, Svil, and Itgb3bp.
Keywords: buněčné dělení; Animals; aparát dělícího vřeténka; Nuclear Proteins; Fam208a; Multipolar spindle apparatus; fosfoproteiny; CRISPR-Cas systémy; jaderné proteiny; HEK293 Cells; Gene Expression Regulation, Developmental; Genomic Instability; Mice, Knockout; CRISPR-Cas Systems; myši knockoutované; Zygote; zygota; lidé; Phosphoproteins; Mice; letální geny; malá interferující RNA; myši; HEK293 buňky; Humans; HUSH; Embryonic Development; RNA, Small Interfering; Multiprotein Complexes; Genes, Lethal; RNA Interference; nestabilita genomu; Spindle Apparatus; Genome stability; zvířata; embryonální vývoj; RNA interference; Mice, Inbred C57BL; Cell Division; vývojová regulace genové exprese; myši inbrední C57BL; multiproteinové komplexy